Promotion of Weather Resilient Technologies, Practices, and Services: Gram Crop - CGIAR Research Program on Climate Change, Agriculture and Food Security; BAIF Development Research Foundation (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Improved drought-resilient crop variety of gram crop was introduced and promoted in the project district of Betul, in Madhya Pradesh. This led to increased crop production and assured income of farmers, even during drought situations.